SUSTAINABLE MAINTENANCE OF AGING REINFORCED CONCRETE STRUCTURES: EVALUATING DIAGNOSTIC TECHNIQUES FOR EARLY DETECTION OF REINFORCEMENT CORROSION - Alexandre Lorenzi; Luciani Somensi Lorenzi; Lucas Alexandre Reginato; Luiz Carlos Pinto da Silva Filho (Mix Sustentável)
Reinforcement corrosion is a critical issue affecting the durability of reinforced concrete structures, particularly in Brazilian urban buildings now 40 to 50 years old. Sustainable management of these aging structures is essential to extend their service life and reduce the environmental impact of demolition and reconstruction. Repairing these structures, rather than demolishing them, significantly lowers the consumption of raw materials and construction waste, aligning with sustainability principles. Early corrosion detection is crucial for timely maintenance, helping preserve structural integrity and avoid unnecessary replacements, further minimizing environmental impacts. This study, part of a doctoral thesis, evaluates diagnostic techniques based on corrosion potential measurements to support sustainable infrastructure management. Full-scale reinforced concrete beams were subjected to induced corrosion using the Modified Immersion Accelerated Corrosion (CAIM) method, targeting 5%, 10%, and 15% mass loss levels. The results showed significant uncertainty in corrosion potential diagnostics at 5% and 10% mass loss, making early-stage assessments inconclusive. However, at 15% mass loss, the method produced satisfactory results, indicating its reliability at more advanced stages. The study highlights the need for more accurate diagnostic tools for early corrosion detection to promote sustainable maintenance and reduce environmental and economic costs from structural failure and replacement.